Developing social competence held in primary teacher inclusive education - Iswari, Mega (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2017)
His study aims to develop social competence in elementary school teacher who organizes the educational system inclusions. As for the problems that often arise for teachers in schools is the lack of knowledge of teachers of children with special needs who become learners. Due to a variety of disorders experienced by learners. Thus it is necessary the development of social competence of teachers in order handling Children with special needs who would require special education services as well. This study was conducted to train elementary school teachers who organize educational inclusion. This type of research is the development of research carried out systematically, field tests, evaluated and improved to meet the prescribed criteria in terms of quality, effectiveness. Development procedures used to follow the steps of research and development put forward by Borg Gall (1983: 775).The results of this study proved that through training can develop social competence elementary school teacher education Inclusion in Padang, It is evident from the scores of teachers are given training before the average score of 78.8571 with n = 42, while the mean scores after receiving training average score increased to 87.5476. means social competence of teachers evolved into having the ability to communicate effectively with students, with fellow educators and fellow educators and parents and the community. Thus the social competence of elementary school teachers in developing after receiving training on Inclusion education provision for children with special needs.